The ‘4V’ Approach in Strategic Human Resources Management Post- COVID -19 - Supratim Chowdhury (International Journal of Engineering and Management Research, 2020)
The ‘4V’ approach is administered throughout the operational level in an organisation. Expression of empathy among all levels of the hierarchy of the taskforce is the foundation of this ‘4V’approach and need of the hour. The proposed ‘4V’ approach is a continual process; it requires continuous support and initiative of top management for transforming organisational work environment. It is peak time for top management's leadership to instigate and develop a candour relationship between its people and the organisation's vision. The approach addresses and dilutes the psychological distress of the workforce arising from the deadly COVID -19 pandemic. In this research, the '4V' approach is a strategic-compliances deliberation, that is developed based on 'Managerial Good Practices' within the operational system of the organisation. The study also confirms upon offering a pious work environment to every individual in the organisation. Comprehending the detailed analysis of each 'V' of the '4V'approach, it is definite that the '4V'approach is psychologically administered. The uncertainty of COVID-19 is raising without any specific deadline, in this scenario its judicious to accept the new normalness and get our systems ready in parlance with COVID-19 management at the workplace. The need of the hour is to enhance flexibility and adaptability to accept the conscious changes in life along with re-imaging and innovative ideas to restructure the business setbacks s due to the COVID -19 pandemic. Making the employee feel safe, at ease, imperative to the organisation, ought to be the prime concern of this strategic HR approach and ensuring combating-traits among people against the pandemic situation.